Capitalism and environment:: can they really co-exist? (Sustainability in Debate, 2017)
Marques, Luiz. Capitalismo e colapso ambiental. Campinas: Editora da Unicamp, 2015. 64 p. ISBN: 9788526812741. Preço: R$ 80.